Landslide Disaster Mitigation Education In Primary School Children - Purnomosutji Dyah Prinajati iin (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
Landslides often occur in highland areas. This disaster cause casualties, including children. Children are vulnerable to become victims of disasters. This research has the main purpose to find out children’s knowledge about landslides and landslide mitigation as well as possible preventive measures that can do to prevent the landslide happen. The type of research is descriptive qualitative that used questionnaire method. The research wa held at SDN Cipayung 07, sample consist of fifth and sixth grade children. The level of knowledge about landslides and landslide mitigation was categorized into low, moderate, and high. The research was found out that 27 respondents(45%) are have high knowledge about landslide, 18 respondents (30%) are moderate, and 15 respondents (25%) have low knowledge about landslide. At the same time, 19 respondents (31.67%) have high knowledge about landslide mitigation, 25 respondents (41.67%) are moderate, and 16 respondents (26.67%) have low knowledge about landslide mitigation. Landslide prevention can be done by use gabion to hold the soil, close the land cracks with solid soil, reduce the thickness of the soil, plant the lands with the suitable plants, put the stones on the path, and make a good drainage channels on the land. Keywords: Education, awareness, student